Processo de gestão financeira em arranjos produtivos locais - Uezato, Carolina Yumi [UNESP]; Santos, David Ferreira Lopes [UNESP]; Borges, Ana Claudia Giannini [UNESP]; Brumatti, Lívia Martinez [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The current work has as a goal presenting the procces of elaborating a guide to business credit orientation, taking form of an educational booklet, which is the first stage to carry out the Extension Project that includes training and advising companies from Local Clusters. The material contains the steps of the process and the caring needed when getting credit. The purpose of this booklet is presenting relevant information in order to create a positive influence on a businessman or entrepreneur, so he can use his debt in the best way he can. For the development of this work, the information has been taken from financial management books and online data bases from the main financial institutions of the country. In the creating process of the guide, it was possible to observe that the options of credit are varied and offered by multiple banks. There is a tendency for the commercial banks to offer short terms credit lines; these options turn back to the need of working capital, however, when analyzing this from the books, it appears that this situation can cause the “scissors effect” on the company. In this way, the guide tries to elucidate the different needs of financing with the respective credit lines, so that the entrepreneur or micro entrepreneur can use the financial leverage to increase his return and not to destroy it. Besides, it was possible to realize the relevance of BNDES and others development institutions like “Banco do Povo” e “Agência Paulista de Desenvolvimento (Desenvolve SP)” in lending to Brazilian companies.

O presente trabalho teve por objetivo apresentar o processo de elaboração de um guia para orientação de crédito empresarial em forma de cartilha educativa, que é a primeira etapa para a efetivação do Projeto de Extensão, o qual compreende formação e assessoria para as empresas dos Arranjos Produtivos Locais (APL). O material contém as etapas do processo e cuidados na obtenção de crédito. O objetivo da cartilha é apresentar informações relevantes com o intuito de influenciar positivamente o empresário, para que este utilize sua dívida da melhor maneira possível. Para o desenvolvimento da cartilha, foram utilizadas informações retiradas de livros de administração financeira, bases de dados online e sites das principais instituições financeiras do país. No processo de formulação do guia foi possível observar que existem opções variadas de obtenção de crédito, sendo elas oferecidas por múltiplas instituições financeiras. Há uma tendência nos bancos comerciais em oferecerem linhas de crédito de curto prazo; estas opções de financiamento voltam-se para necessidades de capital de giro, porém quando analisada com a literatura, verificase que esta situação pode ocasionar o “efeito tesoura” nas empresas. Desta forma, o guia procura elucidar as diferentes necessidades de financiamento com as respectivas linhas, de modo que o empreendedor ou microempresário possa utilizar a alavancagem financeira para aumentar o seu retorno e não para destruí-lo. Nesse sentido, foi possível constatar a importância do BNDES e de outras instituições públicas de fomento, como o Banco do Povo e a Agência Paulista de Desenvolvimento (Desenvolve SP), na concessão de crédito às empresas brasileiras.
Keywords: Financial education; Lines of credit; Financial instituitions; Educação financeira; Linhas de crédito; Instituições financeiras